PsHint1, associated with the G‐protein α subunit PsGPA1, is required for the chemotaxis and pathogenicity of Phytophthora sojae - Zhang, Xin (John Wiley and Sons Inc., 2015)

(untitled) (Mol Plant Pathol)
Zoospore chemotaxis to soybean isoflavones is essential in the early stages of infection by the oomycete pathogen Phytophthora sojae. Previously, we have identified a G‐protein α subunit encoded by PsGPA1 which regulates the chemotaxis and pathogenicity of P. sojae. In the present study, we used affinity purification to identify PsGPA1‐interacting proteins, including PsHint1, a histidine triad (HIT) domain‐containing protein orthologous to human HIT nucleotide‐binding protein 1 (HINT1). PsHint1 interacted with both the guanosine triphosphate (GTP)‐ and guanosine diphosphate (GDP)‐bound forms of PsGPA1. An analysis of the gene‐silenced transformants revealed that PsHint1 was involved in the chemotropic response of zoospores to the isoflavone daidzein. During interaction with a susceptible soybean cultivar, PsHint1‐silenced transformants displayed significantly reduced infectious hyphal extension and caused a strong cell death in plants. In addition, the transformants displayed defective cyst germination, forming abnormal germ tubes that were highly branched and exhibited apical swelling. These results suggest that PsHint1 not only regulates chemotaxis by interacting with PsGPA1, but also participates in a Gα‐independent pathway involved in the pathogenicity of P. sojae.